Hill Soils of Bankura District, West Bengal - Banerjee, A. K. (Indian Forester, 1971)
Hill soils of Bankura District have been studied. The mineralogical composition of the parent rock and its relation to the mechanical and chemical composition of the soil have been discussed. The nutrient status of the soil particularly with respect to N, P and K has been indicated.